Application of the Cooperative Script Learning Model to Improve Student Learning Outcomes in Basic Competencies Understanding the Concept of Implementation and Supervision of Building Construction Work at SMK Negeri 1 Hilliserangkai for the 2022/2023 Acad - Berkat Setiaman Halawa; Aprianus Telaumbanua; Yelisman Zebua (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Implementation and Supervision of Construction and Property is an important subject to be mastered by students at school. But in fact, Class XI students at SMK Negeri 1 Hiliserangkai experience problems in this study, namely the application of the Cooperative Script learning model has not been optimally implemented. So that student learning outcomes in the basic competency of Understanding the Concept of Implementation and Supervision of Building Construction Work are still relatively low and do not meet the specified Minimum Completeness Criteria is 70. The objectives of this study are (1) To describe the implementation of the learning process by applying the Cooperative Script learning model, ( 2) To find out the increase in student learning outcomes in basic competencies Understanding the Concept of Implementation and Supervision of Building Construction Work in Class XI of the Construction and Property Business Department of SMK Negeri 1 Hiliserangkai through the application of the Cooperative Script learning model. This type of research is Classroom Action Research. This research was conducted at SMK Negeri 1 Hiliserangkai with research subjects in class XI students of the Construction and Property Business Department semester I of the 2022/2023 academic year with a total of 12 students. Research instruments (1) Observation sheets consist of (a) observation sheets (Teacher Respondents) (b) Observation sheets of students' activeness in the learning process. (2) Learning achievement test (3) Photo documentation. The results of the study (1) the first cycle (1) the average observation of the learning process (teacher respondents) was 78.12%, (2) the average observation of student activity in the learning process was 60.15% had not reached the specified target, the average -the average student learning outcomes of 67.5% are classified as sufficient categories, the percentage of student learning completeness is 25%. (2) Cycle II (1) the average observation of the learning process (teacher respondents) was 95.31%, (2) the average observation of student activity was 78.9%, the average student learning outcomes was 92.52% classified as very good category, the percentage of student learning completeness is 100%, has reached the set target of 70%. From the results of the research above, it can be concluded that by applying the Cooperative Script Learning Model to the Basic Competency of Understanding the Concept of Implementation and Supervision of Building Construction Work it can improve student learning outcomes for Class XI students of SMK Negeri 1 Hiliserangkai in the 2022/2023 Academic Year.